Go to the scene: TH9 cells superior migration ability to the lungs explains their exceptional anticancer efficacy - Lionel Apetoh; Jiazhi Xu (Journal for ImmunoTherapy of Cancer)
Antibodies against immune checkpoints are now routinely administered as a first line of treatment against metastatic lung cancer. Resistance to immune checkpoint inhibitors is, however, frequent, underscoring the need to find alternative treatments. Adoptive T-cell therapy has recently proven effective in treating patient’s refractory to immune checkpoint inhibitors. This provides impetus to characterize the T-cell subsets best able to tackle tumors. The anticancer activities of IL-9-producing CD4 T helper cells (TH9 cells) were identified in melanoma in 2012. TH9 cells feature strong antimelanoma effects thanks to their production of interleukin (IL)-9 and the activation of innate and adaptive immune effectors. The ability of TH9 cells to prevent the growth of triple-negative breast cancer (TNBC) and osteosarcoma (OS), which commonly metastasize to the lungs, is elusive. In this commentary, we discuss the findings of Chen et al reported in the JITC demonstrating that TH9 cells are lung-tropic and eliminate TNBC and OS cells developing in the lungs. We also highlight how these investigations are in line with recent studies indicating that the adoptive transfer of IL-9-producing T cells eliminate aggressive cancers, including hematological tumors like leukemia and solid tumors such as glioblastoma. Altogether, these findings over the past 13 years support the clinical evaluation of TH9 cells in the adoptive therapy of cancer.